DAYA DUKUNG ULTIMIT PONDASI DANGKAL DI ATAS TANAH PASIR YANG DIPERKUAT GEOGRID - Pontjo Utomo (Institute of Research and Community Outreach - Petra Christian University, 2004)
This research was conducted to compare the ultimate bearing capacity of square footing and strip footing rested on geogrid-reinforced sand via model test in the laboratory. The parameters studied were the top layer depth of geogrid below the footing (u), vertical spacings of geogrid layers (z) and the depth of the deepest geogrid layer (d) below the footing. For both square and strip footing, the value of u/B = 0.25-0.5 (B = width of footing) can give benefit to the ultimate bearing capacity of sand up to 2.5-3.5 times greater than unreinforced sand. On the value of z/B = 0.5, on the square footing case, could increase the bearing capacity up to 3.5 times bigger than unreinforced sand, while on the strip footing, z/B = 0.25 increase the ultimate bearing capacity up to 2.5 times greater than unreinforced case. At the value of d/B = 1.5, both square and strip footing could give benefits which amplified the ultimate bearing capacity up to 5 times and 3 times bigger than unreinforced sand respectively. Abstract in Bahasa Indonesia : Penelitian ini dilakukan untuk membandingkan kapasitas daya dukung ultimit pondasi bujur sangkar dan pondasi lajur yang berada di atas tanah pasir yang diperkuat geogrid melalui uji model di laboratorium. Parameter yang diteliti meliputi efek letak lapisan geogrid teratas (u), efek spasi geogrid (z) dan efek letak lapisan terbawah (d) dari geogrid terhadap kenaikan daya dukung ultimit pondasi. Untuk model pondasi baik bujur sangkar maupun lajur, nilai u/B = 0.25-0.5 (B = lebar pondasi) mampu meningkatkan daya dukung ultimit hingga 2.5-3.5 kali daya dukung ultimit tanah pondasi tanpa perkuatan. Nilai z/B = 0.5 pada pondasi bujur sangkar memberikan kenaikan daya dukung hingga 3.5 kali lipat dan pondasi lajur, nilai z/B = 0.25 memberikan kenaikan daya dukung hingga 2.5 kali lipat. Nilai d/B = 1.5, pada pondasi bujur sangkar dan lajur mampu menaikkan daya dukung tanah pondasi hingga 5 kali lipat dan 3 kali lipat dibanding tanah tanpa perkuatan.